Importación de lámparas inflables solares desde Estados Unidos - Acevedo Castro, María José (2016)
The importation of inflatable solar lamps from the USA aims to introduce a new source of light to our country. The product will be directed to the rural sectors and distributors of camping accessories. The inflatable lamps are characterized by generating light using solar panels, without the need to use electricity to charge them. The product allows us to obtain an environmentally friendly source of light. These lamps are of easy transportation due to the fact that their size can be reduced and for being lightweight. It is important to mention that the Tariff Heading taken from the Integrated National Tariff for the inflatable solar lamps was chosen for the method of function, reinforced by the explanatory notes corresponding to the 4th Recommendation of Amendment. I will undertake statistical investigations of importation of the last five years, taken from the chosen Heading Tariff, established in the principle pages of economic statistics such as the Central Bank and Trade Map.